Standarisasi Ekstrak Etanol Buah Bintaro (Cerbera odollam Gaertn.) Sebagai Obat Tradisional - Rezki Amriati Syarif; Virsa Handayani; Alfirah Angraeni (Faculty of Pharmacy, Universitas Muslim Indonesia, 2022)
This research was conducted with the aim of examining the utilization of bintaro fruit extract (Cerbera odollam Gaertn.) as a traditional medicine that meets quality standards, so that the extract standardization process was carried out by determining specific and non-specific parameters.Based on the enormous potential of the Bintaro plant as a natural ingredient that can be used as traditional medicine, it is necessary to standardize the Bintaro fruit extract to determine the quality and safety of the extract raw materials used to support health. The research was conducted by determining the standardization of data on the determination of specific and non-specific parameters. The specific parameters that have been carried out include the identity of the extract, organoleptic test, the content of water soluble compounds 19.7%, the content of ethanol soluble compounds 6.96%, the content of positive extract compounds containing alkaloids, flavonoids, terpenoids, tannins and saponins. Non-specific parameters that have been carried out include drying shrinkage of 0.197%, moisture content of 2.124%, total ash content of 3.65%, acid soluble ash content of 1.3%, metal contamination of Pb and Cd 0.02 µg/g, microbial contamination of ALT bacteria. 0 colonies and 20 colonies of yeast. The results of the study met the standardization of extract quality.The data that will be obtained is expected to be additional information about the ethanolic extract of bintaro fruit (Cerbera odollam Gaertn.) that meets quality standards as traditional medicine, so as to maintain consistency and uniformity of efficacy and keep active compounds consistently measurable between treatments, and can maintain safety on consumers.